Adequacy of the pension system: A qualitative interview of Indonesian civil service pensioners in Kapuas Regency - Abdul Hadi; Yogi Vidyattama; Badriah Badriah; Prihoda Emese (Economies, 2024)
Around three million pensioners receive the Indonesian civil service pension benefit. This benefit is the main source of income for the majority of civil service pensioners. This paper examines the adequacy of this pension benefit from the perspective of pensioners in Kapuas Regency. Through qualitative research, fifteen semi-structured interviews were conducted to investigate the role of pension benefits in maintaining the interviewees' lifestyles and standards of living. All the interviewees perceived that the pension benefit could cover their basic needs, but for most of them, it only covered 25% of their total expenditures. Despite this, the replacement rate of the take-home pay from the pension benefit is still acceptable based on the ILO standard. While some can adjust to life with basic needs, others choose to find another source of income after retirement. Therefore, although the amount is still higher than the poverty line and the minimum wage, the findings suggest the retirement rate is considered meager.
Keywords: H05; H06; H55; 330; adequacy; perception; civil service pensioners; pension system; Indonesia